Mitigation of cogging torque in surface permanent magnet brushless DC motor using slot opening shift - Patel, A. N.; Panchal, T. H. (National Technical University "Kharkiv Polytechnic Institute" and Аnatolii Pidhornyi Institute of Power Machines and Systems of NAS of Ukraine, 2026)
Introduction. Cogging torque deteriorates the torque quality of surface permanent magnet brushless DC (PMBLDC) motors. Problem. Reducing cogging torque is indispensable for performance upgradation of PMBLDC motors; hence, it is an important issue for motor designers. Goal. This paper presents a slot opening shift approach to reduce the cogging torque of radial flux surface PMBLDC motors. Methodology. A 200 W, 1000 rpm radial flux surface PMBLDC motor is first designed based on different assumed design variables and is treated as a reference model. The parallel stator teeth are uniformly distributed along the stator periphery, and the slot opening is considered in the middle position in the reference design. The cogging torque of the reference design is obtained from simulation and electromagnetic analysis. Results. A series of finite element simulations are performed to examine the impact of design upgradation on the cogging torque of the surface PMBLDC motor. It is observed that the peak-to-peak cogging torque is reduced by 44.5 %. Scientific novelty. The design is enhanced by applying slot opening shift to stator slots. The slot opening is shifted in an anticlockwise direction, and subsequently, the cogging torque waveform is determined for the upgraded motor from finite element modelling and analysis. Practical value. Research has revealed that this technique is effective in reducing cogging torque, and it can also be applied to other topologies of permanent magnet motors. References 23, tables 2, figures 12.